The Study of CNS Manifestations in Aluminium Phosphide Poisoning - Khurana, Puneet; Gupta , Anju (Journal of Indian Academy of Forensic Medicine, 2015)
With rapid development in the field of science & technology and green revolution in the agricultural sector, the problem of acute aluminium phosphide poisoning leading to morbidity and mortality is spreading like a wild fire. Different disciplines of medical science are working on various aspects both from treatment as well as preventive point of view. Aluminium Phosphide is a very toxic, cheap, ideal suicidal and lethal protoplasmic poison involving all generations and organ systems of the body. Although its incidence was unknown before 1980 but now it has surpassed every other poisoning in India especially in the northern states and has created havoc with the human lives. Our study showed that males (1.94:1) are the major sufferer with high mortality rate (76%). The freshness of tablet and lack of specific antidote are directly related to its poor prognosis. Major CNS manifestations are dizziness (52%) and headache (44%). Loss of consciousness is only the terminal event and sufficient time is available to record the dying declaration. Magnesium sulphate has some role in its management.